2020
DOI: 10.1039/d0ra07195a
|View full text |Cite|
|
Sign up to set email alerts
|

Application of soot discharged from the combustion of marine gas oil as an anode material for lithium ion batteries

Abstract: Many studies have recently investigated the characteristics of combustion products emitted from ships and onshore plant facilities for use as energy sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Gunture et al extracted ONC from DS, which exhibited spherical geometry and looked like an onion-like structure, as shown in Figure H . Additionally, the BC emitted from merchant and aircraft engines showed multilayered spherical particles in a continuous network with approximate sizes in the range of 30–40 nm (Figure I), as studied by Baek et al Choi et al reported the isolation of BC from diesel-powered merchant ships and used it as an anodic material for LIBs based on its conducting nature. The TEM image of soot shows a spherical morphology, and particles were aggregated into chain structures .…”
Section: Spectroscopic and Microscopic Analysis Of Bc-derived Nanocar...mentioning
confidence: 92%
See 4 more Smart Citations
“…Gunture et al extracted ONC from DS, which exhibited spherical geometry and looked like an onion-like structure, as shown in Figure H . Additionally, the BC emitted from merchant and aircraft engines showed multilayered spherical particles in a continuous network with approximate sizes in the range of 30–40 nm (Figure I), as studied by Baek et al Choi et al reported the isolation of BC from diesel-powered merchant ships and used it as an anodic material for LIBs based on its conducting nature. The TEM image of soot shows a spherical morphology, and particles were aggregated into chain structures .…”
Section: Spectroscopic and Microscopic Analysis Of Bc-derived Nanocar...mentioning
confidence: 92%
“…The LIB rate performance was investigated via CV analysis, and it was observed that the response of this CV curve is identical with that recommended for capacitive chargestorage behavior, as shown in Figure 13B at scan rates of 0.2− 1.0 mV s −1 . 52 A new form of soot collected from coal tar is also categorized as a pollutant soot source. This is also used as a carbon source for nanocarbon fabrication because it has an interconnected porous structure and rich oxygen-containing functional groups.…”
Section: Applications Of Pollutant-soot-derived Nanocarbonmentioning
confidence: 99%
See 3 more Smart Citations